Adding age-adjusted shock index to the American College of Surgeons' trauma team activation criteria to predict severe injury in children. Issue 2 (20th February 2023) - McCormick, Taylor; Haukoos, Jason; Hopkins, Emily; Trent, Stacy; Adelgais, Kathleen; Cohen, Mitchell; Gausche-Hill, Marianne
Abstract : In this cohort of pediatric trauma registry patients, the addition of shock index, pediatric adjusted to the ACS-6 for trauma team activation resulted in significantly increased sensitivity for emergency operative or procedural intervention or ISS >15 but poor specificity. Abstract : BACKGROUND: The American College of Surgeons (ACS) requires trauma centers to use six minimum criteria (ACS-6) for full trauma team activation. Our goal was to evaluate the effect of adding age-adjusted shock index (SI) to the ACS-6 for the prediction of severe injury among pediatric trauma patients with the hypothesis that SI would significantly improve sensitivity with an acceptable decrease in specificity. METHODS: We performed a secondary analysis of prospectively collected EMS and trauma registry data from two urban pediatric trauma centers. Age-adjusted SI thresholds were calculated as heart rate divided by systolic blood pressure using 2020 Pediatric Advanced Life Support SI vital sign ranges and previously published Shock Index, Pediatric Adjusted (SIPA) thresholds. The primary outcome was a composite of emergency operative (within 1 hour of arrival) or emergency procedural intervention (EOPI) or Injury Severity Score (ISS) greater than 15. Sensitivities, specificities, and 95% CIs were calculated for the ACS-6 alone and in combination with age-adjusted SI. RESULTS: There were 8, 078 patients included; 20% had an elevated age-adjusted SI and 17% met at least one ACS minimum criterion; 1% underwent EOPI; and 17% had ISS >15. Sensitivity and specificity of the ACS-6 for EOPI or ISS > 5 were 45% (95% confidence interval [CI], 41–50%) and 89% (95% CI, 81–96%). Inclusion of Pediatric Advanced Life Support-SI and SIPA resulted in sensitivities of 51% (95% CI, 47–56%) and 69% (95% CI, 65–72%), and specificities of 80% (95% CI, 71–89%) and 60% (95% CI, 53–68%), respectively. Similar trends were seen for each secondary outcome. CONCLUSION: In this cohort of pediatric trauma registry patients, the addition of SIPA to the ACS-6 for trauma team activation resulted in significantly increased sensitivity for EOPI or ISS greater than 15 but poor specificity. Future investigation should explore using age-adjusted shock index in a two-tiered trauma activation system, or in combination with novel triage criteria, in a population-based cohort. LEVEL OF EVIDENCE: Diagnostic Tests or Criteria; Level II. Abstract :